Individual factors and vection in younger and older adults: How sex, field dependence, personality, and visual attention do (or do not) affect illusory self-motion - Brandy Murovec; Julia Spaniol; Behrang Keshavarz (i-Perception)
An important aspect to an immersive experience in Virtual Reality is vection, defined as the illusion of self-motion. Much of the literature to date has explored strategies to maximize vection through manipulations of the visual stimulus (e.g., increasing speed) or the experimental context (e.g., framing of the study instructions). However, the role of individual differences (e.g., age, biological sex) in vection susceptibility has received little attention. The objective of the current study was to investigate the influence of individual-difference factors on vection perception in younger and older adults. Forty-six younger adults ( M age  = 25.1) and 39 older adults ( M age  = 72.4) completed assessments of personality traits, field dependence, and visual attention prior to observing a moving visual stimulus aimed at inducing circular vection. Vection was measured using self-reports of onset latency, duration, and intensity. Results indicated that, in both age groups, females experienced longer-lasting vection compared to males. Additionally, the level of field dependence was related to vection intensity and duration in males but not in females. Variability in vection intensity was best explained by a mixture of biological, perceptual, cognitive, and personality variables. Taken together, these findings suggest that individual factors are important for understanding differences in vection susceptibility.